Positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery

By using lithium transition metal composite oxides with high Ni content and carbon nanotubes in the positive electrode of nonaqueous electrolyte secondary battery, combined with appropriate particle size and morphological design, the capacity of lithium transition metal composite oxides in the charge and discharge cycle is solved. The problem of reducing increases the energy density and service life of the battery.

CN113410428BActive Publication Date: 2025-01-03PANASONIC HOLDINGS CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110270598.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2021-03-12
Publication Date
2025-01-03
Estimated Expiration
2041-03-12

AI Technical Summary

Technical Problem

The lithium transition metal composite oxide with high Ni content has a problem of reduced capacity during the charge and discharge cycle, and the prior art is difficult to effectively suppress this phenomenon.

Method used

Using the positive electrode of the nonaqueous electrolyte secondary battery containing lithium transition metal composite oxide with high Ni content, the particle size and particle morphology of the lithium transition metal composite oxide are controlled to ensure conductivity. and fill capacity suppress the reduction in capacity during the charge and discharge cycle.

Benefits of technology

It effectively suppresses the reduction of the capacity of the nonaqueous electrolyte secondary battery in the charging and discharging cycle, improves the energy density and conductivity of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113410428B_ABST
    Figure CN113410428B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery. As an example of the present invention, the positive electrode for a non-aqueous electrolyte secondary battery comprises a positive electrode active material and carbon nanotubes, wherein the positive electrode active material comprises: a lithium transition metal composite oxide (I), which is a secondary particle formed by agglomerating primary particles with an average particle size of 1 μm or more, or substantially composed of a single particle, and the volume-based median particle size (D50) is 0.6 μm to 6 μm; and a lithium transition metal composite oxide (II), which is a secondary particle formed by agglomerating primary particles with an average particle size of less than 1 μm, and the volume-based median particle size (D50) is 3 μm to 25 μm, wherein the lithium transition metal composite oxides (I) and (II) contain more than 80 mol% of Ni relative to the total molar number of metal elements other than Li, and the particle surfaces of the oxides (I) and (II) respectively have one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery. Background Art

[0002] In recent years, lithium transition metal composite oxides with high Ni content have attracted much attention as positive electrode active materials with high energy density. For example, Patent Document 1 discloses a non-aqueous electrolyte secondary battery comprising a composite oxide as a positive electrode active material, wherein the composite oxide has Ni and Li as main components and has a general formula of Li x Ni 1-p-q-r Co p Al q A r O 2-y (A is at least one element selected from the group consisting of Ti, V, In, Cr, Fe, Sn, Cu, Zn, Mn, Mg, Ga, Ni, Co, Zr, Bi, Ge, Nb, Ta, Be, Ca, Sr, Ba, and Sc), and is composed of primary particles of a single crystal having an average particle size of 2 μm to 8 μm.

[0003] In addition, Patent Document 2 discloses a lithium metal composite oxide powder, which is composed of secondary particles formed by agglomeration of primary particles and single particles existing independently of the secondary particles, and when the number of single particles is a and the number of secondary particles is b, [a / (a+b)] satisfies 0.5<[a / (a+b)]<1.0. Patent Document 2 states that by using this lithium transition metal composite oxide powder, particle rupture caused by pressurization during positive electrode forming is suppressed, and charge-discharge cycle characteristics are improved.

[0004] In addition, Patent Document 3 discloses a positive electrode active material, the particle surface of which is covered with lithium metaborate and nickel oxide, and the coverage of lithium metaborate is 85% or more and less than 95%. Patent Document 3 states that by using this positive electrode active material, the side reaction between the active material and the electrolyte is suppressed, and the rate characteristics are improved.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2006-54159

[0008] Patent Document 2: Japanese Patent Application Publication No. 2019-160571

[0009] Patent Document 3: Japanese Patent Application Publication No. 2013-137947 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] However, lithium transition metal composite oxides having a high Ni content are required to suppress the decrease in capacity accompanying charge and discharge cycles. Even when the techniques of Patent Documents 2 and 3 are used, the decrease in capacity accompanying charge and discharge cycles cannot be sufficiently suppressed.

[0012] An object of the present invention is to suppress a decrease in capacity associated with charge and discharge cycles of a nonaqueous electrolyte secondary battery by using a positive electrode for a nonaqueous electrolyte secondary battery comprising a lithium transition metal composite oxide having a high Ni content.

[0013] Solutions for solving problems

[0014] A positive electrode for a non-aqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it comprises: a positive electrode core, and a positive electrode composite material layer arranged on the aforementioned positive electrode core, the aforementioned positive electrode composite material layer contains a positive electrode active material and carbon nanotubes, the aforementioned positive electrode active material contains: a lithium transition metal composite oxide (I), which is a secondary particle formed by aggregation of primary particles with an average particle size of 1 μm or more, or is substantially composed of a single particle, and the volume-based median particle size (D50) is 0.6 μm to 6 μm; and a lithium transition metal composite oxide (II), which is a secondary particle formed by aggregation of primary particles with an average particle size of less than 1 μm, and the volume-based median particle size (D50) is 3 μm to 25 μm, the aforementioned lithium transition metal composite oxides (I) and (II) contain 80 mol% or more of Ni relative to the total molar number of metal elements other than Li, and at least one element selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table exists on the particle surfaces of the oxides (I) and (II), respectively.

[0015] A nonaqueous electrolyte secondary battery as one embodiment of the present invention includes a positive electrode and a negative electrode and a nonaqueous electrolyte, wherein the positive electrode is the positive electrode for the nonaqueous electrolyte secondary battery.

[0016] Effects of the Invention

[0017] By using the positive electrode for a nonaqueous electrolyte secondary battery of the present invention, it is possible to suppress a decrease in capacity associated with charge and discharge cycles of the nonaqueous electrolyte secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0019] Figure 2 It is a schematic cross-sectional view showing an example of a positive electrode used in a nonaqueous electrolyte secondary battery as an embodiment. DETAILED DESCRIPTION

[0020] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery of the present invention will be described in detail. Hereinafter, a cylindrical battery is exemplified in which a wound electrode body is housed in a bottomed cylindrical outer shell can, but the outer shell is not limited to a cylindrical outer shell can, and for example, it may be a square outer shell can, or it may be an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with separators.

[0021] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes: a wound electrode body 14, a nonaqueous electrolyte, and a can 16 for storing the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 sandwiched therebetween. The can 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the can 16 is regarded as the lower side.

[0022] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may also contain a halogen substituted substance in which at least a portion of the hydrogen in these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6. It should be noted that the electrolyte is not limited to a liquid electrolyte, and may also be a solid electrolyte using a gel-like polymer or the like.

[0023] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are wound into a spiral shape so as to be alternately stacked along the radial direction of the electrode body 14. In order to prevent the precipitation of lithium, the negative electrode 12 is preferably formed with a size that is one circle larger than the positive electrode 11. That is, the negative electrode 12 is preferably formed longer than the positive electrode 11 in the longitudinal direction and the width direction (transverse direction). The separator 13 is formed, for example, with a size that is at least one circle larger than the positive electrode 11, and two separators 13 are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0024] Insulating plates 18 and 19 are disposed above and below the electrode body 14, respectively. Figure 1In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.

[0025] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. The outer can 16 is formed with a groove portion 22 for supporting the sealing body 17, with a part of the side portion extending inward. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and supports the sealing body 17 with its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove portion 22 and the open end of the outer can 16 to which the sealing body 17 is fastened.

[0026] The sealing body 17 has the following structure: an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central parts, and an insulating member 25 is sandwiched between their respective peripheral parts. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and ruptured, pushing the upper valve body 26 to the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 ruptures, and the gas is discharged from the opening of the cover 27.

[0027] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 will be described.

[0028] [positive electrode]

[0029] Figure 2 Schematic cross-sectional view showing an example of a positive electrode used in a non-aqueous electrolyte secondary battery as an embodiment. Figure 2 As shown in the example, the positive electrode 11 includes: a positive electrode core 30, and a positive electrode composite material layer 31 disposed on the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, or a thin film having the metal disposed on the surface. The positive electrode composite material layer 31 includes a positive electrode active material, a binder, and a conductive material. Figure 2As shown, the positive electrode composite material layer 31 can be provided on a single side of the positive electrode core 30, but is preferably provided on both sides of the positive electrode core 30. The positive electrode 11 can be manufactured, for example, as follows: a positive electrode composite material slurry containing a positive electrode active material, a binding material, and a conductive material is applied to the surface of the positive electrode core 30, and after the coating is dried, it is pressed to form the positive electrode composite material layer 31 on both sides of the positive electrode core 30.

[0030] The conductive material contained in the positive electrode composite material layer 31 includes carbon nanotubes. It can be considered that by making the positive electrode composite material layer 31 include carbon nanotubes, even when using the positive electrode active material containing the lithium transition metal composite oxide (I) and (II) with a high Ni content described later, the conductivity between the particles of the positive electrode active material can be ensured, and the reduction of the battery capacity during the charge and discharge cycle can be suppressed. In addition, when carbon nanotubes are used as conductive materials, compared with the use of granular conductive materials such as acetylene black, the conductivity between the particles of the positive electrode active material can be ensured even if the amount of conductive material added is reduced, so the filling amount of the positive electrode active material is increased, and the energy density of the battery can also be improved.

[0031] For carbon nanotubes, single-layer carbon nanotubes and multi-layer carbon nanotubes can be cited. Single-layer carbon nanotubes (SWCNT) are carbon nanostructures in which one layer of graphene sheets constitutes one cylindrical shape in the form of one layer. Multi-layer carbon nanotubes are carbon nanostructures in which multiple layers of graphene sheets are stacked in concentric circles to form a cylindrical shape. It should be noted that graphene sheets refer to layers in which the carbon atoms of the sp2 hybrid orbits constituting the graphite crystal are located at the vertices of a regular hexagon. There is no limitation on the shape of carbon nanotubes. As the shape, various forms including needle-like, cylindrical, fishbone (fishbone or cup-stacked), flake (trump) and coil-like can be cited.

[0032] The positive electrode composite material layer 31 may include only one of single-layer carbon nanotubes and multi-layer carbon nanotubes, but from the perspective of improving the conductivity between the particles of the positive electrode active material and further suppressing the capacity reduction in the charge and discharge cycle, it is preferred to include both single-layer carbon nanotubes and multi-layer carbon nanotubes. It is generally believed that single-layer carbon nanotubes have longer fiber lengths than multi-layer carbon nanotubes, so by making the positive electrode composite material layer 31 include single-layer carbon nanotubes, it is easy to ensure the conductive path between the particles of the positive electrode active material. In addition, it is generally believed that single-layer carbon nanotubes have high flexibility because the fiber diameter is thinner than that of multi-layer carbon nanotubes. By making the positive electrode composite material layer 31 include single-layer carbon nanotubes, it is possible to follow the expansion and contraction of the active material during the charge and discharge cycle, and maintain the contact between the active material particles. In addition, it is generally believed that by making the positive electrode composite material layer 31 include multi-layer carbon nanotubes with a fiber length shorter than that of single-layer carbon nanotubes, it is easy to form a plurality of contact points between multi-layer carbon nanotubes and particles of the positive electrode active material. In addition, it is generally believed that by making the positive electrode composite material layer 31 include multilayer carbon nanotubes with a fiber diameter thicker than the single-layer carbon nanotubes, the contact area between the multilayer carbon nanotubes and the particles of the positive electrode active material is easily widened. Therefore, it can be considered that compared with using only single-layer carbon nanotubes or only multilayer carbon nanotubes, the conductivity between the particles of the positive electrode active material is improved, and the reduction of the battery capacity during the charge and discharge cycle can be further suppressed.

[0033] The fiber length of single-walled carbon nanotubes is, for example, 10 to 50 μm, and the fiber length of multi-walled carbon nanotubes is, for example, 1 to 20 μm. It should be noted that the fiber length of carbon nanotubes can be obtained by measuring the lengths of any 50 carbon nanotubes using a field emission scanning microscope (FE-SEM) and calculating the arithmetic average.

[0034] The fiber diameter of a single-walled carbon nanotube is, for example, 1 nm to 5 nm, and the fiber diameter of a multi-walled carbon nanotube is, for example, 5 nm to 30 nm. The fiber diameter of a carbon nanotube can be obtained by measuring the outer diameters of any 50 carbon nanotubes using a field emission scanning microscope (FE-SEM) or a transmission electron microscope (TEM) and calculating the arithmetic average.

[0035] The ratio of the mass of the single-layer carbon nanotubes to the mass of the positive electrode composite material layer 31 is preferably smaller than the ratio of the mass of the multi-layer carbon nanotubes to the mass of the positive electrode composite material layer 31. That is, in terms of mass, the positive electrode composite material layer 31 preferably contains fewer single-layer carbon nanotubes than multi-layer carbon nanotubes (in other words, preferably contains more multi-layer carbon nanotubes than single-layer carbon nanotubes). This can sometimes further suppress the reduction in battery capacity during charge and discharge cycles.

[0036] The positive electrode composite material layer 31 may contain a granular conductive material, but preferably does not contain a granular conductive material. By making the positive electrode composite material layer 31 free of granular conductive materials, the filling amount of the positive electrode active material is increased, and sometimes the energy density of the battery is improved. It should be noted that, as a granular conductive material, for example, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be exemplified. When using a granular conductive material, its primary particle size is preferably 5 nm or more and 100 nm or less, and the aspect ratio is preferably less than 10.

[0037] Examples of the binder contained in the positive electrode composite material layer 31 include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF); polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. These resins can be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0038] The positive electrode active material contained in the positive electrode composite material layer 31 includes: a lithium transition metal composite oxide (I) having a volume-based median particle size (D50) of 0.6 μm to 6 μm, and a lithium transition metal composite oxide (II) having a volume-based median particle size (D50) of 3 μm to 25 μm (hereinafter referred to as "composite oxides (I) and (II)"). The positive electrode active material may include only composite oxides (I) and (II), and may also include composite oxides or other compounds other than composite oxides (I) and (II) within the scope of not impairing the purpose of the present invention.

[0039] The volume-based median particle size (D50) refers to the particle size at which the cumulative frequency of the smaller particle size in the volume-based particle size distribution reaches 50%, and is also called the median particle size. The particle size and particle size distribution of the composite oxide can be measured using a laser diffraction particle size distribution measuring device (e.g., Microtrac Bel Co., Ltd., MT3000II) and water as a dispersion medium.

[0040] Composite oxide (I) is a secondary particle formed by the aggregation of larger primary particles having an average particle size of 1 μm or more, or a composite oxide particle consisting essentially of a single particle. Composite oxide (I) consisting essentially of a single particle refers to a particle in which the grain boundaries of the primary particles cannot be confirmed when observed at an appropriate magnification using a scanning electron microscope (SEM). When composite oxide (I) is a secondary particle, the average particle size of the primary particles is, for example, 1 μm to 6 μm. Composite oxide (II) is a secondary particle formed by the aggregation of smaller primary particles having an average particle size of less than 1 μm.

[0041] When the composite oxide (I) is a secondary particle, the grain boundary of the primary particle can be confirmed in the cross section of the particle observed by SEM. The composite oxide (I) is composed of, for example, less than 100, preferably several to dozens, and more preferably 2 to 5 primary particles, and the composite oxide (II) is composed of, for example, 10,000 to 5,000,000 primary particles. The particle size of the primary particles can be measured as the Feret diameter of the area (primary particle) surrounded by the grain boundary in the SEM image of the cross section of the composite oxide particles. The average particle size of the primary particles is obtained by averaging the particle sizes of 100 primary particles.

[0042] The composite oxide (I) contains more than 80 mol% of Ni relative to the total molar number of metal elements other than Li. In addition, the particle surface of the composite oxide (I) contains more than one element selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table. In addition, the composite oxide (II) also contains more than 80 mol% of Ni relative to the total molar number of metal elements other than Li, and the particle surface of the composite oxide (II) contains more than one element selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table. These elements present on the particle surface are in the state of compounds such as metals, alloys, or oxides. The particle surface refers to the primary particle surface and the secondary particle surface. It should be noted that a portion of one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table may be present inside the primary particles of the composite oxide and form a solid solution together with other metal elements contained in the composite oxide.

[0043] Examples of group 4 elements include Ti (titanium), Zr (zirconium), and Hf (hafnium). Examples of group 5 elements include V (vanadium), Nb (niobium), and Ta (tantalum). Examples of group 6 elements include Cr (chromium), Mo (molybdenum), and W (tungsten). Examples of group 13 elements include B (boron), Al (aluminum), Ga (gallium), In (indium), and Tl (thallium).

[0044] By using the composite oxides (I) and (II) having the above-mentioned particle size and particle morphology as the positive electrode active material, for example, the particle breakage associated with the rolling of the positive electrode active material when making the positive electrode 11 can be suppressed. In addition, by making the above-mentioned elements present on the particle surface of the composite oxides (I) and (II), for example, the side reaction with the non-aqueous electrolyte can be suppressed, and the particle breakage of the positive electrode active material can be suppressed. It can be considered that the suppression of such particle breakage is beneficial for suppressing the reduction of battery capacity during the charge and discharge cycle. Therefore, it can be considered that due to the synergistic effect between the suppression of particle breakage of the positive electrode active material produced by using the composite oxides (I) and (II) having the above-mentioned particle size and particle morphology and the ensuring of the conductivity between the particles of the positive electrode active material produced by using the aforementioned carbon nanotubes, even if a lithium transition metal composite oxide with a high Ni content is used, the reduction of battery capacity during the charge and discharge cycle can be suppressed.

[0045] As the composite oxide (I), for example, from the viewpoint of increasing the energy density of the battery and suppressing the decrease in battery capacity during the charge and discharge cycle, a general formula Li a Ni b Co c M1 d M2 e O f (wherein, 0.8≤a≤1.2, b≥0.80, c≤0.15, 0.01≤d≤0.12, 0.001≤e≤0.06, 1≤f≤2, b+c+d+e=1, M1 is one or more elements selected from Mn and Al, and M2 is one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table), and it is particularly preferred that M2 in the above general formula is one or more elements selected from B and Al. The molar fraction of the metal element in the entire particle of the composite oxide can be measured by inductively coupled plasma (ICP) emission spectrometry analysis.

[0046] The composite oxide (I) can be produced, for example, by the following steps.

[0047] A lithium compound such as lithium hydroxide as a Li source and a nickel-containing compound as a Ni source are mixed in a mixing ratio based on the target composite oxide (I), a potassium compound or a sodium compound is added to the mixture, and roasting is performed in the atmosphere or in an oxygen gas flow (process 1). The nickel-containing compound may contain other added elements such as Mn and Al. Then, the obtained roasted product is washed with water to remove the potassium compound or sodium compound attached to the surface of the roasted product, and a compound containing one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table is added to the obtained lithium-containing nickel composite oxide, so that one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table are compounded on the particle surface, and then roasting is performed (process 2). The compounding uses a dry particle compounding device (e.g., Hosokawa Micron Co., Ltd. system, NOB-130) and the like. During the compounding, a lithium source such as lithium hydroxide can be added.

[0048] By the above method, a composite oxide (I) having one or more elements selected from Groups 4, 5, 6, and 13 of the periodic table on the surface of the particles is synthesized. The detailed theory of the increase in primary particle size is unknown, but it is believed that when a potassium compound or a sodium compound is added to the above mixture, the growth of single crystal particles during calcination proceeds uniformly throughout the mixture phase.

[0049] The calcination temperature in step 1 is, for example, 600° C. to 1050° C., and there is a tendency that the primary particles become larger as the temperature increases. The calcination time in step 1 is, for example, about 1 to 100 hours. Examples of potassium compounds include potassium hydroxide (KOH) and its salts, potassium acetate, and the like. Examples of sodium compounds include sodium hydroxide and its salts, and the like. For example, potassium compounds and sodium compounds are added in an amount of 0.1 to 100% by mass or less relative to the synthesized composite oxide (I).

[0050] The calcination temperature in step 2 is, for example, 200° C. to 500° C. The lower the temperature, the more elements of Group 4, Group 5, Group 6, and Group 13 of the periodic table can be present on the particle surface. The calcination time in step 2 is, for example, about 1 to 100 hours.

[0051] As an example of the composite oxide (II), for example, from the viewpoint of increasing the energy density of the battery and suppressing the decrease in battery capacity during the charge and discharge cycle, the general formula Li a Ni b Co c M1 d M2 e O f(wherein, 0.8≤a≤1.2, b≥0.80, c≤0.15, 0.01≤d≤0.12, 0.001≤e≤0.06, 1≤f≤2, b+c+d+e=1, M1 is one or more elements selected from Mn and Al, and M2 is one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table) is a composite oxide represented by, and it is particularly preferred that M2 in the above general formula is one or more elements selected from B and Ti.

[0052] The composite oxide (II) can be produced, for example, by the following steps.

[0053] A lithium compound such as lithium hydroxide as a Li source and a nickel-containing compound as a Ni source are mixed in a mixing ratio based on the target composite oxide (II), and roasted in the atmosphere or in an oxygen gas stream (process 1). The nickel-containing compound may include other added elements such as Mn and Al. A compound containing one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table is added to the resulting roasted product (lithium-containing nickel composite oxide), so that one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table are composited on the particle surface, and then roasted (process 2). During composite, a lithium source such as lithium hydroxide may be added.

[0054] By the above method, a composite oxide (II) having one or more elements selected from Groups 4, 5, 6 and 13 of the periodic table on the particle surface is synthesized. The calcination time and calcination temperature in steps 1 and 2 are the same as those in the synthesis of the composite oxide (I).

[0055] For composite oxide (II), for example, from the viewpoint of suppressing the decrease in battery capacity during charge and discharge cycles, it is preferred that B is included as M2 in the above general formula, and when particles having a particle size greater than 70% of the particle size (D70) based on the volume are used as the first particles and particles having a particle size less than 30% of the particle size (D30) based on the volume are used as the second particles, the molar fraction (B1) of B in the first particles relative to the total number of moles of metal elements other than Li is greater than the molar fraction (B2) of B in the second particles relative to the total number of moles of metal elements other than Li. In composite oxide (II), B is usually present on the particle surface in the form of a B-containing compound. The boron compound may also contain Li.

[0056] Among them, D70 refers to the particle size when the cumulative frequency from the smaller particle size in the volume-based particle size distribution reaches 70%. Similarly, D30 refers to the particle size when the cumulative frequency from the smaller particle size in the volume-based particle size distribution reaches 30%. For example, D70 is 9μm to 19μm, and D30 is 3μm to 13μm.

[0057] The ratio (B1 / B2) of the molar fraction of boron (B1) contained in the first particle to the molar fraction of boron (B2) contained in the second particle is preferably 1.1 or more, more preferably 1.5 or more, and may be 3.0 or more. The upper limit of (B1 / B2) is not particularly limited, and is, for example, 10. An example of the range of (B1 / B2) is 1.5 to 3.5 or 2.5 to 3.5.

[0058] Hereinafter, an example of a method for producing a composite oxide (II) in which the mole fraction (B1) of B in the first particle relative to the total mole number of metal elements other than Li is greater than the mole fraction (B2) of B in the second particle relative to the total mole number of metal elements other than Li is described.

[0059] A lithium compound such as lithium hydroxide is added to two nickel-containing compounds (X1) and (X2) having different D50s, respectively, and the mixtures are calcined to synthesize lithium nickel composite oxides (Y1) and (Y2) having different D50s (step 1). The nickel-containing compound may contain other additive elements such as Mn and Al.

[0060] The obtained lithium nickel composite oxides (Y1) and (Y2) may be washed with water.

[0061] Next, a boron source is added to the lithium nickel composite oxides (Y1) and (Y2), respectively, and the boron is composited on the particle surface and then calcined to synthesize lithium transition metal composite oxides (Z1) and (Z2) (process 2). Then, the composite oxides (Z1) and (Z2) are mixed to obtain a composite oxide (II). An example of a boron source is boric acid (H3BO3). During the composite, a lithium source such as lithium hydroxide can be added.

[0062] In the above step 2, the amount of H3BO3 added to the lithium nickel composite oxide (Y1) is greater than the amount of H3BO3 added to the lithium nickel composite oxide (Y2), thereby obtaining a state in which the mole fraction (B1) of boron on the surface of the first particle and the second particle of the composite oxide (II) is greater than the mole fraction (B2). The calcination temperature in the above step 2 is, for example, 200° C. to 500° C.

[0063] The coverage of the boron compound on the surface of the first and second particles of the composite oxide (II) can be adjusted by whether the composite oxides (Y1) and (Y2) are washed with water and by adjusting the calcination temperature. The washed composite oxides (Y1) and (Y2) are calcined at high temperature together with a boron source to synthesize a composite oxide with a small surface coverage of the boron compound. The high temperature refers to, for example, 350°C to 500°C.

[0064] The content of the composite oxide (I) relative to the mass of the positive electrode active material is, for example, 5 to 65 mass %, preferably 10 to 60 mass %, and particularly preferably 20 to 55 mass %. The content of the composite oxide (II) relative to the mass of the positive electrode active material is, for example, 35 to 95 mass %, preferably 40 to 90 mass %, and particularly preferably 45 to 80 mass %.

[0065] The resistance value of the positive electrode mixture layer 31 is preferably 15 Ωcm, for example, from the viewpoint of suppressing a decrease in battery capacity during a charge and discharge cycle. 2 Less than, more preferably 10Ωcm 2 The following is the result. For example, by including carbon nanotubes in the positive electrode composite material layer 31, the resistance value of the positive electrode composite material layer 31 can be reduced. The resistance value of the positive electrode composite material layer 31 can be measured using an electrode resistance measurement system RM2610 manufactured by Hioki Electric Co., Ltd.

[0066] The density of the positive electrode composite material layer 31 is preferably 3.55 g / cc or more, more preferably 3.60 g / cc or more, for example, from the perspective of high energy density of the battery. For example, by making the content of the composite oxides (I) and (II) within the above range, the packing density of the positive electrode composite material layer 31 can be increased.

[0067] [negative electrode]

[0068] The negative electrode 12 has: a negative electrode core, and a negative electrode composite material layer provided on the surface of the negative electrode core. The negative electrode core can be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal on the surface. The negative electrode composite material layer contains a negative electrode active material and a binding material, and is preferably provided on both sides of the negative electrode core except for the portion connected to the negative electrode lead 21. The negative electrode 12 can be made, for example, as follows: a negative electrode composite material slurry containing a negative electrode active material and a binding material is applied to the surface of the negative electrode core, and after the coating is dried, it is rolled to form a negative electrode composite material layer on both sides of the negative electrode core.

[0069] The negative electrode composite material layer contains, for example, a carbon-based active material that reversibly absorbs and releases lithium ions as a negative electrode active material. The carbon-based active material is, for example, natural graphite such as flaky graphite, block graphite, and earthy graphite, block artificial graphite (MAG), and graphitized mesophase carbon microbeads (MCMB) and other artificial graphites. In addition, the negative electrode active material can use a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material can be used in combination.

[0070] The binding material contained in the negative electrode composite material layer is the same as that in the positive electrode 11, and fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc. can also be used, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode composite material layer preferably further includes CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, SBR and CMC or its salt, PAA or its salt can be used in combination.

[0071] [Separator]

[0072] The separator 13 may be, for example, a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the separator 13 includes polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 may be a single-layer structure or a laminated structure. A heat-resistant layer may be formed on the surface of the separator.

[0073] Example

[0074] Hereinafter, the present invention will be further described based on examples, but the present invention is not limited to these examples.

[0075] <Example 1>

[0076] [Preparation of composite oxide (I)]

[0077] The composition obtained by coprecipitation is Ni 0.82 Co 0.10 Mn 0.08 The nickel-cobalt-manganese composite hydroxide of (OH)2 is calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide. Next, lithium hydroxide is mixed with the prepared nickel-cobalt-manganese composite oxide in a molar ratio of Li to the total amount of Ni, Co, and Mn of 1.05:1, and further, a potassium compound is added to the mixture in an amount of 20% by mass relative to the composite oxide. The mixture is calcined at 750°C in an oxygen atmosphere for 72 hours, then crushed, and washed with water to remove the potassium compound, thereby obtaining a composite oxide. The composite oxide is dry-mixed with a boron compound in a molar ratio of the total amount of Ni, Co, and Mn to B of the boron compound of 100:1.0, so that B is compounded on the surface of the particles, and then calcined at 300°C in an oxygen atmosphere for 8 hours. The calcined product is crushed to obtain a composite oxide (I) having B on the surface of the particles.

[0078] The composition of the composite oxide (I) was analyzed by ICP, and the results showed that Li 1.01 Ni 0.81 Co 0.10 Mn 0.08 B 0.01O2. It should be noted that the D50 value of the composite oxide (I) is 4 μm. The cross section of the composite oxide (I) after CP processing was confirmed by SEM observation. As a result, the average particle size of the primary particles of the composite oxide (I) was 2 μm. About 50% or more of all the particles of the composite oxide (I) were single particle structures, and some particles had aggregate structures formed by combining 3 to 10 primary particles.

[0079] [Preparation of Composite Oxide (II)]

[0080] The composition obtained by coprecipitation is Ni 0.85 Co 0.08 Mn 0.07 The nickel-cobalt-manganese composite hydroxide of (OH)2 is calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide. Subsequently, lithium hydroxide is mixed with the prepared nickel-cobalt-manganese composite oxide in a molar ratio of Li to the total amount of Ni, Co, and Mn of 1.08:1. The mixture is calcined at 700°C in an oxygen atmosphere for 8 hours and then crushed to obtain a composite oxide. The composite oxide, a boron compound, and a titanium compound are dry-mixed in a molar ratio of 100:1:2 between the total amount of Ni, Co, and Mn and B in the boron compound and Ti in the titanium compound, so that B and Ti are compounded on the surface of the particles, and then calcined at 300°C in an oxygen atmosphere for 8 hours. The calcined product is crushed to obtain a composite oxide (II) having B and Ti on the surface of the particles.

[0081] The composition of the composite oxide (II) was analyzed by ICP, and the results showed that Li 1.01 Ni 0.83 Co 0.08 Mn 0.07 B 0.01 Ti 0.02 O2. D50 of the composite oxide (II) was 11 μm. The cross section of the composite oxide (II) after the CP treatment was observed by SEM, and the average particle size of the primary particles of the composite oxide (II) was 0.5 μm.

[0082] The obtained composite oxide (II) was mixed with the composite oxide (I) in an amount of 50 mass % based on the total mass of the positive electrode active material to prepare a positive electrode active material.

[0083] [Production of positive electrode]

[0084] The above-mentioned positive electrode active material, single-layer carbon nanotubes (SWCNT), multi-layer carbon nanotubes (MWCNT) and polyvinylidene fluoride (PVdF) are mixed at a solid content mass ratio of 98.76:0.04:0.2:1.0, and after adding an appropriate amount of N-methyl-2-pyrrolidone (NMP), they are kneaded to prepare a positive electrode composite material slurry. The positive electrode composite material slurry is applied to both sides of the positive electrode core formed by aluminum foil, and after the coating film is dried, the coating film is rolled with a roller and cut into a specified electrode size to obtain a positive electrode having a positive electrode composite material layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.

[0085] [Production of negative electrode]

[0086] Natural graphite is used as the negative electrode active material. The negative electrode active material is mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite material slurry. The negative electrode composite material slurry is applied to both sides of a negative electrode core formed of copper foil, and after the coating film is dried, the coating film is rolled with a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode composite material layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode.

[0087] [Preparation of non-aqueous electrolyte]

[0088] Lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 3:3:4. Furthermore, vinylene carbonate (VC) was dissolved at a concentration of 2.0 mass % in the mixed solvent to prepare a non-aqueous electrolyte.

[0089] [Battery production]

[0090] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode. The positive electrode and the negative electrode are wound into a spiral shape with a polyolefin separator sandwiched therebetween, and then pressed in a radial direction to produce a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate sheet, and the non-aqueous electrolyte is injected, and the opening of the outer shell is sealed to obtain a non-aqueous electrolyte secondary battery.

[0091] <Example 2>

[0092] [Preparation of Composite Oxide B]

[0093] The composition obtained by coprecipitation is Ni 0.85 Co 0.08 Mn0.07 The nickel-cobalt-manganese composite hydroxide (OH)2 was calcined at 500°C and then sieved using a vibrating sieve machine (mesh size 300 μm, shaking time 30 minutes) to obtain a nickel-cobalt-manganese composite oxide (X1) with a residual D50 of 14 μm on the sieve and a nickel-cobalt-manganese composite oxide (X2) with a sieved D50 of 7 μm.

[0094] Next, lithium hydroxide and nickel-cobalt-manganese composite oxide (X1) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08: 1. The mixture was calcined at 700° C. for 8 hours in an oxygen atmosphere and then pulverized to obtain lithium composite oxide (Y1).

[0095] Separately, lithium hydroxide and nickel-cobalt-manganese composite oxide (X2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08: 1. The mixture was calcined at 700° C. for 8 hours in an oxygen atmosphere and then pulverized to obtain a lithium composite oxide (Y2).

[0096] Next, the lithium composite oxide (Y1), the boron compound and the titanium compound are dry mixed in a manner such that the total amount of Ni, Co and Mn and the molar ratio of B in the boron compound to Ti in the titanium compound are 100:1.5:3, so that B and Ti are compounded on the particle surface. The mixture is calcined at 300°C in an oxygen atmosphere for 8 hours and then pulverized to obtain a lithium composite oxide (Z1) having B and Ti on the particle surface.

[0097] In addition, lithium composite oxide (Y2), boron compound and titanium compound are dry mixed in a manner such that the total amount of Ni, Co and Mn and the molar ratio of B in the boron compound to Ti in the titanium compound are 100:0.5:1, so that B and Ti are compounded on the particle surface. The mixture is calcined at 300°C in an oxygen atmosphere for 8 hours and then pulverized to obtain lithium composite oxide (Z2) with B and Ti on the particle surface. Then, lithium composite oxide (Z1) and (Z2) are mixed in a mass ratio of 1:1 to obtain composite oxide (II).

[0098] In the composite oxide (II), the molar fraction (B1) of boron in the first particle having a particle size larger than D70 on a volume basis is 0.015, and the molar fraction (B2) of boron on the surface of the second particle having a particle size smaller than D30 on a volume basis is 0.005, and the ratio (B1 / B2) is 3.0. In addition, the coverage of boron on the surface of the first particle and the second particle is 96%. The amount of boron (molar fraction) contained in the first particle and the second particle is measured by ICP. In addition, the amount of boron present on the particle surface (surface coverage) is measured by EPMA.

[0099] The composition of the composite oxide (II) was analyzed by ICP, and the results showed that Li 1.01 Ni 0.83 Co 0.08 Mn 0.07 B 0.01 Ti 0.02 O2. It should be noted that D50 of the composite oxide (II) was 11 μm. The cross section of the composite oxide (II) after CP processing was confirmed by SEM observation, and the average particle size of the primary particles of the composite oxide (II) was 0.5 μm.

[0100] In Example 2, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that a positive electrode active material was used in which the composite oxide (I) obtained in Example 1 was mixed with the composite oxide (II) in an amount of 50 mass % relative to the total mass of the positive electrode active material.

[0101] <Example 3>

[0102] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that an aluminum compound was used instead of a boron compound in the preparation of the composite oxide (I). It should be noted that the composition of the composite oxide (I) of Example 3 was analyzed by ICP, and the result was Li 1.01 Ni 0.81 Co 0.10 Mn 0.08 Al 0.01 The D50 and the average particle size of the primary particles of the composite oxide (I) were the same as those in Example 1.

[0103] <Example 4>

[0104] In the preparation of the positive electrode, the positive electrode active material obtained in Example 1, single-layer carbon nanotubes (SWCNT), multi-layer carbon nanotubes (MWCNT) and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 98.76:0.2:0.04:1.0. Except for this, a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1.

[0105] <Example 5>

[0106] In the preparation of the positive electrode, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the positive electrode active material obtained in Example 1, single-walled carbon nanotubes (SWCNT) and polyvinylidene fluoride (PVdF) were mixed at a solid content mass ratio of 98.96:0.04:1.0.

[0107] <Example 6>

[0108] In the preparation of the positive electrode, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the positive electrode active material obtained in Example 1, multiwalled carbon nanotubes (MWCNT) and polyvinylidene fluoride (PVdF) were mixed at a solid content mass ratio of 98.8:0.2:1.0.

[0109] <Example 7>

[0110] In the preparation of the positive electrode, the positive electrode active material obtained in Example 1, single-layer carbon nanotubes (MWCNT), acetylene black (AB) and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 98.76:0.04:0.2:1.0, and a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1.

[0111] <Example 8>

[0112] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that a tantalum compound was used instead of a titanium compound in the preparation of the composite oxide (II). It should be noted that the composition of the composite oxide (II) of Example 8 was analyzed by ICP, and the result was Li 1.01 Ni 0.83 Co 0.08 Mn 0.07 B 0.01 Ta 0.01 The D50 and the average particle size of the primary particles of the composite oxide (II) were the same as those in Example 1.

[0113] <Example 9>

[0114] A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that a tungsten compound was used instead of a titanium compound in the preparation of the composite oxide (II). It should be noted that the composition of the composite oxide (II) of Example 9 was analyzed by ICP, and the result was Li 1.01 Ni 0.83 Co 0.08 Mn 0.07 B 0.01 W 0.01 The D50 and the average particle size of the primary particles of the composite oxide (II) were the same as those in Example 1.

[0115] <Example 10>

[0116] In the preparation of composite oxide (I), titanium compound was added together with boron compound, and dry mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of B of boron compound to Ti of titanium compound was 100:1:2, so that B and Ti were composited on the particle surface; in addition, titanium compound was not added in the preparation of composite oxide (II), and a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1. It should be noted that the composition of composite oxide (I) of Example 10 was analyzed by ICP, and the result was Li 1.01 Ni 0.81 Co 0.10 Mn 0.8 B 0.01 Ti 0.02 O2. In addition, the composition of the composite oxide (II) of Example 10 was analyzed by ICP, and the result was Li 1.01 Ni 0.84 Co 0.08 Mn 0.07 B 0.01 The D50 and average particle size of the primary particles of the composite oxides (I) and (II) are the same as those in Example 1.

[0117] <Example 11>

[0118] In the preparation of composite oxide (I), tantalum compound was added together with boron compound, and dry mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of B of boron compound to Ta of tantalum compound was 100:1:2, so that B and Ta were composited on the particle surface; in addition, titanium compound was not added in the preparation of composite oxide (II), and a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1. It should be noted that the composition of composite oxide (I) of Example 11 was analyzed by ICP, and the result was Li 1.01 Ni 0.81 Co 0.10 Mn 0.08 B 0.01 Ta 0.02 O2. In addition, the composition of the composite oxide (II) of Example 11 was analyzed by ICP, and the result was Li 1.01 Ni 0.84 Co 0.08 Mn 0.07 B 0.01 The D50 and average particle size of the primary particles of the composite oxides (I) and (II) are the same as those in Example 1.

[0119] <Example 12>

[0120] In the preparation of composite oxide (I), a tungsten compound was added together with a boron compound, and dry-mixed in a manner such that the total amount of Ni, Co, and Mn and the molar ratio of B of the boron compound to W of the tungsten compound was 100:1:2, so that B and W were composited on the particle surface; in addition, no titanium compound was added in the preparation of composite oxide (II), and a non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1. It should be noted that the composition of composite oxide (I) of Example 12 was analyzed by ICP, and the result was Li 1.01 Ni 0.80 Co 0.10 Mn 0.08 B 0.01 W 0.02 O2. In addition, the composition of the composite oxide (II) of Example 12 was analyzed by ICP, and the result was Li 1.01 Ni 0.85 Co 0.08 Mn 0.07 B 0.01 The D50 and average particle size of the primary particles of the composite oxides (I) and (II) are the same as those in Example 1.

[0121] <Comparative Example 1>

[0122] In the preparation of the positive electrode, a nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the positive electrode active material obtained in Example 1, acetylene black (AB) and polyvinylidene fluoride (PVdF) were mixed at a solid content mass ratio of 98.8:0.2:1.0.

[0123] [Charge and discharge cycle test]

[0124] Each battery of the embodiment and the comparative example was charged at a constant current of 0.5 It until the battery voltage reached 4.2 V, and charged at a constant voltage of 4.2 V until the current value reached 1 / 50 It. Then, the battery was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge and discharge cycle was repeated 150 times.

[0125] For each battery of the example and the comparative example, the discharge capacity at the 1st cycle and the discharge capacity at the 150th cycle of the above cycle test were determined, and the capacity retention rate was calculated based on the following formula. The results are summarized in Table 1.

[0126] Capacity retention rate (%) = (150th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100

[0127] (Evaluation of resistance of positive electrode composite material layer)

[0128] The resistance value of each positive electrode composite material layer prepared in Examples and Comparative Examples was measured by cutting each positive electrode into a 20 mm×20 mm shape with a tab, using an electrode resistance measurement system RM2610 manufactured by Hioki Electric Co., Ltd. The results are summarized in Table 1.

[0129] [Table 1]

[0130]

[0131] As shown in Table 1, compared with the battery of the comparative example, the battery of the embodiment has a high capacity retention rate after the charge and discharge cycle test, and the capacity reduction associated with the charge and discharge cycle is suppressed. In addition, compared with the positive electrode composite material layer of the comparative example, the positive electrode composite material layer of the embodiment shows a low resistance value.

[0132] Description of Reference Numerals

[0133] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 positive electrode core, 31 positive electrode composite material layer

Claims

1. A positive electrode for a non-aqueous electrolyte secondary battery, comprising: a positive electrode core body, and a positive electrode composite material layer disposed on the positive electrode core body, The positive electrode composite material layer comprises a positive electrode active material and carbon nanotubes, wherein the positive electrode active material comprises: a lithium transition metal composite oxide (I), which is composed of secondary particles and single particles formed by aggregation of primary particles with an average particle size of 1 μm or more, or substantially composed of single particles, and the volume-based median particle size (D50) is 0.6 μm to 6 μm, and the proportion of single particles in all particles of the composite oxide (I) is greater than 50%; and a lithium transition metal composite oxide (II), which is composed of secondary particles aggregated by primary particles with an average particle size of less than 1 μm, and the volume-based median particle size (D50) is 3 μm to 25 μm, The lithium transition metal composite oxides (I) and (II) contain 80 mol% or more of Ni relative to the total molar number of metal elements other than Li, and at least one element selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table exists on the particle surfaces of the oxides (I) and (II), respectively. The lithium transition metal composite oxide (II) is of the general formula Li a Ni b Co c M1 d M2 e O f The composite oxide shown in the formula, wherein 0.8≤a≤1.2, b≥0.80, c≤0.15, 0.01≤d≤0.12, 0.001≤e≤0.06, 1≤f≤2, b+c+d+e=1, M1 is one or more elements selected from Mn and Al, and M2 is one or more elements selected from B and Ti.

2. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The carbon nanotubes include both single-walled carbon nanotubes and multi-walled carbon nanotubes.

3. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The content of the lithium transition metal composite oxide (I) relative to the mass of the positive electrode active material is 20% by mass to 55% by mass.

4. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 2, wherein The ratio of the mass of the single-walled carbon nanotube to the mass of the positive electrode composite material layer is smaller than the ratio of the mass of the multi-walled carbon nanotube to the mass of the positive electrode composite material layer.

5. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The lithium transition metal composite oxide (I) is of the general formula Li a Ni b Co c M1 d M2 e O f The composite oxide shown in the formula, wherein 0.8≤a≤1.2, b≥0.80, c≤0.15, 0.01≤d≤0.12, 0.001≤e≤0.06, 1≤f≤2, b+c+d+e=1, M1 is one or more elements selected from Mn and Al, and M2 is one or more elements selected from Group 4, Group 5, Group 6, and Group 13 of the periodic table.

6. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 5, wherein In the lithium transition metal composite oxide (I), M2 in the general formula is one or more elements selected from B and Al.

7. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 5, wherein In the lithium transition metal composite oxide (I), M2 in the general formula is B and Al, and in the lithium transition metal composite oxide (II), M2 in the general formula is B and Ti.

8. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein The resistance of the positive electrode composite material layer is 15Ωcm 2 the following.

9. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 5, wherein In the lithium transition metal composite oxide (II), M2 in the general formula comprises B, When the particles having a particle size larger than 70% of the particle size (D70) based on volume in the lithium transition metal composite oxide (II) are used as first particles, and the particles having a particle size smaller than 30% of the particle size (D30) based on volume are used as second particles, The mole fraction (B1) of B in the first particles relative to the total number of moles of metal elements other than Li is greater than the mole fraction (B2) of B in the second particles relative to the total number of moles of metal elements other than Li.

10. The positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The positive electrode composite material layer does not contain any granular conductive material. 11 . A non-aqueous electrolyte secondary battery comprising a positive electrode and a negative electrode and a non-aqueous electrolyte, wherein the positive electrode is the positive electrode for a non-aqueous electrolyte secondary battery according to claim 1 .